Kirjailijoiden taloudellinen asema Suomessa 2017 (The financial position of Finnish book authors in 2017) - Mikko Grönlund (The Union of Finnish Writers, 2025)
The Union of Finnish Writers commissioned this study, and the Brahea Centre at the University of Turku conducted it. The study describes the financial position of Finnish book authors in 2017. Its purpose was to get information on their income earned through literary work, and other sources of income related to the writer's work. In addition, the study provides information about the Finnish writer society. The previous similar study was conducted in 2011, and it described the economic situation of writers in 2010.